Hubungan Data Demografi Keluarga dalam Pemberian ASI Esklusif Anak Balita Stunting - Putri dewi suciningtyas; Mira Triharini; Praba Diyan Rachmawati (Pediomaternal Nursing Journal, 2019)
Introduction: Stunting is an important nutritional problem in Indonesia because it has a serious impact on the quality of child development. Stunting is thought to be related to family demographics, and environmental conditions. The purpose of this study is to explain the relationship between family demographic factors including age, occupation, income and number of families with stunting nutritional status.Methods: This Study was Cross-Sectional Study. The population in this study were mothers with stunting toddlers aged 2-5 years at the Puskemas Galis Bangkalan with a total sample of 129 respondents, taken according to the inclusion criteria. The independent variables are age of respondents, education, employment, family members and the dependent variable is stunting nutritional status. Data was collected using a structured questionnaire and observation of respondents. The data were then analyzed using the Rank Spearman test with a significance level of <0.05.Results: The results showed that there was no relationship between age of respondents (p=0.305), education (p=0.712), employment (p=0.261), family members (p=0.153) with  stunting of nutritional status.Conclusion: Factors that affect the health of toddler with the nutritional status of stunting toddlers are very multifactorial so that support is needed across sectors to reduce the stunting of nutritional status.